Religija u evropskim javnim prostorima / Religion in the European Public Spaces: Pravni pregled / Legal Overview - Ferrari, Silvio (Context: Journal of Interdisciplinary Studies, 2022)
This chapter discusses the distinguish between media cases from court cases, concerning Muslims and Sikhs which deal with religious dress codes in the common, political and institutional public spaces. It proves the real issue is not the religious symbol in itself but what it reminds the public of: from the Islamic threat’ to the peaceful Sikh community that rescues the Italian parmesan’, the media give their own interpretation of the events and news related to religious issues, influencing people’s attitudes and common knowledge. Indeed Italian history, characterized by divisions and local arrangements which did not contribute towards creating a strong sense of belonging to the Nation and where the Catholic faith has always been a predominant element of the citizens’ identity has often been an example of pragmatic local solutions and arrangements as regards the effects of religious pluralization, such as the greater visibility of religious dress codes in the public spaces.